The Roman Villa of Tirana (Albania) and Its Mosaics - Elda OMARI (Journal of Mosaic Research, 2018)
Tirana, the capital city of Albania, in Antiquity did not exist as an inhabited centre, simply it was considered a rural area, the residential territory of Dyrrachium patricians, as was Ercolano for Pompeii. In 1972 in Tirana, during the construction of a building, the remains of a rustic villa built in Roman Period were brought to light accidentally, and some of the rooms were decorated with polychrome mosaics. This villa was used for more than four centuries and it has several phases of life, for this reason it was dated by the archaeologists between the end of the 1st and the 5th century AD. The principal goal of the research is the punctual analysis of the mosaics motifs and their contextualization in the Balkan and Adriatic area, to identify the owner and the craftsmen who live and work in it. The second goal is to present to the international scientific community this rustic villa, a unique case for Tirana.